PERACANGAN SISTEM INFORMASI PELAYANAN JASA CUCI MOTOR BERBASIS WEB - Februariyanti, Herny; Setiawan, M. Rubi (Information Technology and Telematics, 2019)
Abstract - In advanced technology, business peoples use technology for the development of their business. There are four types of technology that become pillars in the development of technology, namely communication technology, information technology, transportation technology and medical technology. The four pillars are one of the factors that can help small countries become great countries. With this research the author aims to find out the order process, customer service, and report making in motorbike washing services. The four objectives will be made a system with the PHP and MySQL programming languages as the database to be more effective and efficient in the field of motorbike washing services, so that they will get more value in the business and can compete with existing motorbike washing services. Results obtained from the research from motorbike washing services starts from the order process, then customer service in First In First Out (FIFO), the service is obtained financial statements and customer reports which can be a reference and help leaders to make decisions about their business. Designing information systems using PHP and MySQL by analyzing objects, designing programs, creating databases, making programs, testing programs and evaluating programs.